1999
DOI: 10.1016/s0735-1097(99)00130-8
|View full text |Cite
|
Sign up to set email alerts
|

Natural variability of circulating levels of cytokines and cytokine receptors in patients with heart failure: implications for clinical trials

Abstract: In patients with heart failure the degree of natural variability in circulating cytokine levels increases with time, and is greater for IL-6 than for TNF-alpha. Accordingly, the results of the present study suggest that the sample size needed to show a statistically significant change in the circulating level of a given cytokine will vary depending on the specific cytokine that is being measured, as well as the time period over which that cytokine is being assayed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(72 citation statements)
references
References 38 publications
3
68
0
1
Order By: Relevance
“…A similar difference in intra-individual biological variability could also explain the lack of prognostic value observed for IL-6 in the present study. 38 …”
Section: Tnf-α and LV Reverse Remodeling After Crtmentioning
confidence: 99%
“…A similar difference in intra-individual biological variability could also explain the lack of prognostic value observed for IL-6 in the present study. 38 …”
Section: Tnf-α and LV Reverse Remodeling After Crtmentioning
confidence: 99%
“…The term cytokine is applied to a group of relatively small molecular weight protein molecules (generally [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] which are secreted by cells in response to a variety of stimuli. Classically, cytokines are thought to be secreted by ''producer cells'' and act in an autocrine, juxtacrine, or paracrine fashion to influence the biological behavior of neighboring ''target cells'' [8].…”
Section: Overview Of Cytokines Involved In Heart Failurementioning
confidence: 99%
“…Studies of patients with congestive heart failure (CHF) drawn from the general population have shown that high levels of soluble, circulating TNFRs are found in individuals with CHF and are powerful predictors of mortality independently of established markers of CHF severity (17,18). Circulating levels of TNF␣ and interleukin-6 (IL-6) have also been associated with mortality in CHF (17)(18)(19), although the short-term variability in the circulating levels of these cytokines may make them less useful predictors than soluble TNFRs (sTNFR), which maintain more stable levels (20)(21)(22).…”
mentioning
confidence: 99%